2021
DOI: 10.1101/2021.04.29.442010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The natural stilbenoid (–)-hopeaphenol inhibits cellular entry of SARS-CoV-2 USA-WA1/2020, B.1.1.7 and B.1.351 variants

Abstract: Antivirals are urgently needed to combat the global SARS-CoV-2/COVID-19 pandemic, supplement existing vaccine efforts, and target emerging SARS-CoV-2 variants of concern. Small molecules that interfere with binding of the viral spike receptor binding domain (RBD) to the host ACE2 receptor may be effective inhibitors of SARS-CoV-2 cell entry. Here we screened 512 pure compounds derived from natural products using a high-throughput RBD/ACE2 binding assay and identified (-)-hopeaphenol, a resveratrol tetramer, in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
1
0
0
Order By: Relevance
“…Sera collected from immunized animals were evaluated in a modified high-throughput surrogate neutralization assay that uses homogenous time resolved fluorescence (HTRF) technology, where SARS-CoV-2 spike RBD from WT (USA-WA1/2020), Beta (B.1.351), or Delta (B.1.617.2) variants were assessed for ability to interact with ACE2 protein. In this assay, initial experiments showed that 50% human control plasma (i.e., from individuals without SARS-CoV-2 exposure or COVID-19) had no effect on the HTRF signal, while the control inhibitory antibody REGN10933 (casirivimab) blocked HTRF signal due to WT, Beta, or Delta variant RBDs in the presence of human plasma with half-maximal inhibitory concentrations (IC50s) of 47.3, 937.5, and 35.4 ng/mL, consistent with previous reports (33,34). Serial dilutions of day 0 and 41 sera from hamsters were then evaluated for their ability to inhibit binding between ACE2 and the RBD variants of SARS-CoV-2.…”
Section: Immunization Of Syrian Hamsters With Gls-5310 Blocks or Redu...supporting
confidence: 90%
“…Sera collected from immunized animals were evaluated in a modified high-throughput surrogate neutralization assay that uses homogenous time resolved fluorescence (HTRF) technology, where SARS-CoV-2 spike RBD from WT (USA-WA1/2020), Beta (B.1.351), or Delta (B.1.617.2) variants were assessed for ability to interact with ACE2 protein. In this assay, initial experiments showed that 50% human control plasma (i.e., from individuals without SARS-CoV-2 exposure or COVID-19) had no effect on the HTRF signal, while the control inhibitory antibody REGN10933 (casirivimab) blocked HTRF signal due to WT, Beta, or Delta variant RBDs in the presence of human plasma with half-maximal inhibitory concentrations (IC50s) of 47.3, 937.5, and 35.4 ng/mL, consistent with previous reports (33,34). Serial dilutions of day 0 and 41 sera from hamsters were then evaluated for their ability to inhibit binding between ACE2 and the RBD variants of SARS-CoV-2.…”
Section: Immunization Of Syrian Hamsters With Gls-5310 Blocks or Redu...supporting
confidence: 90%